Student’s Thinking Skills At Pesantren - Yuliana, Yuliana; Kusumadewi, Riema Afriani; Gunawan, Heri; Adawiyah, Siti Robiah (Universitas Ahmad Dahlan, 2024)
The learning process in education today tends to be focused on developing a memory of the content of information. Few educational institutions still apply learning methods that can train students' thinking skills to find solutions to solving a problem or making a decision. This research aims to identify learning in building the thinking skills of students at Pondok Pesantren (PP) Darussalam Kunir Subang. This pesantren applies the Kuliyyatul Mu'allimin Al-Islamiyah (KMI) which combines a system of educational methodology and pesantren teaching (salaf/traditional) with modern education. The approach used in this research is qualitative with descriptive methods to identify, describe, and analyze information needs regarding learning in the pesantren. The subjects in this research were four administrators, four teachers, and thirty students at PP Darussalam Kunir Subang. Data collection is done by interview, observation, and documentation. Data analysis includes data reduction, data presentation, and conclusions. The results showed that learning at PP Darussalam Kunir Subang in the form of turats deliberation activities could train students' thinking skills. Th Beside that, project-based teaching and problem-based teaching also can help students develop their thinking skills.